Ultrafine Resveratrol Particles: Supercritical Antisolvent Preparation and Evaluation In Vitro and In Vivo - Kunlun Wang; Xiuhua Zhao; Yuangang Zu; Jialei Li; Xiaonan Zhang; Wei Sun; Xinyang Yu (Advances in Materials Science and Engineering)
Ultrafine resveratrol (u-Res) particles were prepared through the SAS process. The orthogonal method was used to optimize the factors of the SAS process. The size of u-Res reached 0.68 μm under the optimum conditions. The characterization of the u-Res particles was tested by many analysis methods. The chemical structure of Res was unaffected by the SAS process. The degree of crystallinity of the u-Res particles greatly reduced. The purity of the u-Res particles increased from 98.5% to 99.2% during the SAS process. The u-Res particles had greater saturation solubility and dissolution rate than the raw-Res (r-Res) particles. The radical scavenging activity and bioavailability of the u-Res in vivo were 1.9 times of the r-Res.